Exploring patient-provider interactions and the health system’s responsiveness to street-connected children and youth in Kenya: a qualitative study - Embleton Lonnie; Shah Pooja; Gayapersad Allison; Kiptui Reuben; Ayuku David; Wachira Juddy; Apondi Edith; Braitstein Paula (BMC Health Services Research, 2021)
Abstract Background In Kenya, street-connected children and youth (SCY) have poor health outcomes and die prematurely due to preventable causes. This suggests they are not accessing or receiving adequately responsive healthcare to prevent morbidity and mortality. We sought to gain insight into the health systems responsiveness to SCY in Kenya through an in-depth exploration of SCY’s and healthcare provider’s reflections on their interactions with each other. Methods This qualitative study was conducted across 5 counties in western Kenya between May 2017 and September 2018 using multiple methods to explore and describe the public perceptions of, and proposed and existing responses to, the phenomenon of SCY in Kenya. The present analysis focuses on a subset of data from focus group discussions and in-depth interviews concerning the delivery of healthcare to SCY, interactions between SCY and providers, and SCY’s experiences in the health system. We conducted a thematic analysis situated in a conceptual framework for health systems responsiveness. Results Through three themes, context, negative patient-provider interactions, and positive patient-provider interactions, we identified factors that shape health systems responsiveness to SCY in Kenya. Economic factors influenced and limited SCY’s interactions with the health system and shaped their experiences of dignity, quality of basic amenities, choice of provider, and prompt attention. The stigmatization and discrimination of SCY, a sociological process shaped by the social-cultural context in Kenya, resulted in experiences of indignity and a lack of prompt attention when interacting with the health system. Patient-provider interactions were highly influenced by healthcare providers’ adverse personal emotions and attitudes towards SCY, resulting in negative interactions and a lack of health systems responsiveness. Conclusions This study suggests that the health system in Kenya is inadequately responsive to SCY. Increasing public health expenditures and expanding universal health coverage may begin to address economic factors, such as the inability to pay for care, which influence SCY’s experiences of choice of provider, prompt attention, and dignity. The deeply embedded adverse emotional responses expressed by providers about SCY, associated with the socially constructed stigmatization of this population, need to be addressed to improve patient-provider interactions.